Drying Characteristics and Kinetics of Okra at Different Thickness (International Journal of Chemical and Process Engineering Research, 2021)
The effect of sample thickness and temperature on the drying characteristics of okra was investigated using a laboratory moisture analyser (Denver instrument IR-30) at sample thickness of 5mm, 10mm and 15mm and temperatures of 90oC, 100oC and 110oC respectively. The experimental data was fitted into three thin layer mathematical models. The fitness of the experimental data were evaluated using statistical analysis. It was observed that data fitted well with the Page model for the temperatures and sample thicknesses with the highest R2 values of (0.9904, 0.9962, 0.9963); (0.9963. 0.0072, 0.9937); (0.9924, 0.9940, 0.9933) for 5mm-. 15mm thickness at 90oC, 100oC and 110oC respectively with the lowest χ2, MBE and RMSE values. Therefore, Page models adequately described the drying characteristics of okra investigated. The effective moisture ratios were observed to increase with temperature and decrease with okra thickness. The activation energies obtained from Arrhenius equation for 5mm, 10mm and 15mm were 108.7KJ/mol, 118.7KJ/mol and 97.8KJ/mol respectively.